rGO-BCNT/PANI Three-Dimensional Flexible Aerogel Sponge Electrodes and Electrochemical Performance - Wang, Yuhan; Guo, Siyu; Cai, Yanzhi; Hu, Zhongyi; Yu, Haiming; Chen, Dengpeng (Journal of Composites and Biodegradable Polymers, 2023)
Self-supported flexible supercapacitors have promising applications in wearable electronics. The electrode materials, as a crucial component of supercapacitors, have a decisive impact on the energy storage performance of the entire device. Herein, reduced graphene oxide-boron atom doped-carbon nanotubes/polyaniline (rGO-BCNT/PANI) (rBP) three-dimensional (3D) aerogel sponge electrode materials were prepared by a simple ultrasonic self-assembly followed by reduction-induced self-assembly reaction. The rBP aerogel sponge structure not only provided a channel for electrolyte exchange, but also provided enough space for PANI nanoparticles to withstand the volume change during charging and discharging, and inhibited the decomposition of PANI nanoparticles. As a result, the 3D rBP aerogel sponge with 60 mg PANI addition amount (rBP60) exhibited high specific capacitance (695 F·g-1), high power density (675 W·kg-1), and high energy density (60.95 Wh·kg-1) at 0.5 A·g-1 in a three-electrode system. The 3D rBP60 aerogel sponge electrode material can reach 610 F·g-1 at 2 A·g-1, with a retention rate of up to 88% after 2000 cycles. The Coulombic efficiency of the rBP60 aerogel sponge electrode material was close to or equal to 85.5% at different current densities. The 3D rBP aerogel sponge was exceptionally flexible, maintaining its morphology without damage after 100 compression-release cycles.